Current-Mode Full-Wave Rectifier Circuits Using Current Differencing Buffered Amplifier - Erkan, Suleyman; Ayten, Umut Engin; Sagbas, Mehmet (IEEE, 2015)
In this work, a current-mode (CM) full-wave rectifier circuits using only one current differencing buffered amplifier (CDBA) and two diodes are presented. These circuits use only active components which are more suitable for integrated circuit fabrication and posses low input and high output impedances which make it ideal for current-mode systems. The behaviours of the proposed structures are tested by PSPICE simulations for two different types of the CDBA implementation. It is tested by using PSPICE simulations based on the 0.25 mu m TSMC level-7 CMOS technology parameters.
Keywords: Full-wave rectifiers; current differencing buffered amplifier; current mode; active networks; AD844; FLOW GRAPH REALIZATION; PRECISION; FILTER; Engineering; Telecommunications